China's globalization from below : Chinese entrepreneurial migrants and the Belt and Road initiative - Tudoroiu, Theodor, 1964- (London ; New York : Routledge, Taylor & Francis Group, 2022)
"This book analyzes the Chinese-centered globalization 'from below' brought about by China's entrepreneurial migrants and conceived of as a projection of Chinese power in the Belt and Road Initiative partner states. It identifies the features of this globalization 'from below,' scrutinizes its mutually reinforcing relationship with China's globalization 'from above,' and shows that these two globalizations are intrinsically related to the construction of a Chinese-centered international order. It outlines how the actors in China's globalization 'from below' include Chinese emigrants who are located in informal transnational economic networks. It reveals that Beijing has enacted many laws that concern these emigrants and their duty to contribute to the development of their country of origin; and that China is ready to impose harsh punitive actions on political elites in partner states which fail to protect its migrants or limit their economic activities. Finally, it argues that China's globalization 'from below' is fundamentally different from the non-hegemonic globalization 'from below' represented by, among others, Lebanese and East Indian traders, and that rather China's globalization 'from below' is a self-interested national strategy intended to support the construction of a Chinese-centered international order"--
Keywords: Yi dai yi lu (Initiative : China); Chinese -- Government policy -- Foreign countries -- China; Globalization -- China; China -- Emigration and immigration -- Government policy; China -- Foreign economic relations; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research